Determinant Factors of “Eucalyptus globulus” (Labill.) Woodlot Production in Tach Gayint District, South Gondar Zone, Amhara Region, Ethiopia - Addisu Wasie (International Journal of Forestry Research)
Eucalyptus is the most preferred exotic species in different parts of Ethiopia, particularly in the northern part of the country, including the study area. Socioeconomic, institutional, and endowment variables are an influence on the production of this species. The purpose of this study was to identify determinants of Eucalyptus woodlot production for producer farmers in the study area. Multistage sampling techniques were used in order to select the district, kebeles, and household heads to be interviewed. The district and the kebeles were selected purposefully based on their high potential for Eucalyptus production, whereas ninety-six (96) sampled respondent farmers were selected by using simple random sampling techniques. A multiple linear regression (OLS) model was used to run the determinants of Eucalyptus woodlot production, and descriptive statistics were used to describe the socioeconomic characteristics of smallholder Eucalyptus producers in the form of means, frequencies, and percentages. The respondents use Eucalyptus products for construction and fuel wood. Rural farmers produced about 70% of construction wood products and 30% of fuel wood products annually. Five variables (i.e., woodlot size, woodlot density, and market information) significantly affected woodlot production, whereas the age of farmers and market distance were negatively affected. In order to produce better income from Eucalyptus products, the collaboration efforts of all responsible groups (i.e., farmers, researchers, governments, and others) should be required.